Probing nanoscale oxygen ion motion in memristive systems - Yuchao Yang (Nature Portfolio, 2017)
Ion transport in solid-state materials is a fundamental process for many modern technologies. Utilizing electrostatic force microscopy, Yanget al. directly visualize ion motion and verify the oxygen ion dynamics within HfO2—a common metal-oxide based memristive material.